Pedagogical tools to explore Cartesian mind-body dualism in the classroom: philosophical arguments and neuroscience illusions - Hamilton, Scott; Hamilton, Trevor J. (Frontiers in Psychology, 2015)
Please note that this abstract is beyond the maximum allowed word count to address the comments of a reviewer.